Performance Improvement in a Circuit Breaker Mechanism - Arora, Manuj (My University, 2014)
Main design criterion for a circuit breaker is quick and timely disconnection and reconnection of different parts for protection and control. A sluggish response can stress the network thus causing damage to the equipments in a substation. In this study, performance of gas insulated circuit breaker has been improved by minimizing the wipe time of operation. A rigid multi body dynamic simulation model was created in SOLID WORK. All the possible parameters that could influence the wipe time were identified and their effects on the same were further studied. A reduction of 15.8 % in the wipe time and an equivalent reduction of 22.9% in the opening time were reported from the simulated results. Further effect of flexibility of insulating pull rod (made of FRP tube) on travel curve of the contacts was also studied and it was found that flexibility in the pull rod has to be considered for correct prediction of travel characteristics of the circuit breaker contacts. An effort was made to measure the elastic constant of the insulating pull rod and study the effect of improved stiffness on the opening time.
ME-CAD/CAM-Dissertation
Keywords: Circuit breaker; multi body dynamics; mechanism design